1991
DOI: 10.2135/cropsci1991.0011183x003100020015x
|View full text |Cite
|
Sign up to set email alerts
|

Allelism among Genes for Resistance to Soybean Mosaic Virus in Strain‐Differential Soybean Cultivars

Abstract: Five soybean [Glycine max (L.) Merr.] cultivars that have been used to differentiate strain groups of soybean mosaic virus (SMV) were studied to determine the allelic relationships among genes conditioning reaction to SMV. The cultivars PI 96983, ‘Ogden’, ‘York’, ‘Marshall’, and ‘Kwanggyo’ (PI 406710) are each known to have single dominant gene conditioning resistance to SMV. These parents were crossed in all possible combinations with each other and with a susceptible cultivar. The crosses were evaluated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
142
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(156 citation statements)
references
References 0 publications
11
142
0
3
Order By: Relevance
“…PI 96983 was identified as carrying a dominant gene Rsv1 conferring resistance to G1 and a necrotic reaction to G7 (Chen et al 2001(Chen et al , 2002. 'York' was identified to have a single gene Rsv1-y for resistance to G1 but susceptibility to G7 (Chen et al 1991. 'Prolina' and 'Dillon' had the same SMV reaction patterns (resistant to G1 but susceptible to G7) as 'York' and were postulated to carry the same gene (Rsv1-y) that was derived from the ancestor cultivar 'Arksoy' (Zheng et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…PI 96983 was identified as carrying a dominant gene Rsv1 conferring resistance to G1 and a necrotic reaction to G7 (Chen et al 2001(Chen et al , 2002. 'York' was identified to have a single gene Rsv1-y for resistance to G1 but susceptibility to G7 (Chen et al 1991. 'Prolina' and 'Dillon' had the same SMV reaction patterns (resistant to G1 but susceptible to G7) as 'York' and were postulated to carry the same gene (Rsv1-y) that was derived from the ancestor cultivar 'Arksoy' (Zheng et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The four tested Chinese SMV strains/isolates were incapable of infecting 'PI96983', which possesses a resistant locus, Rsv1 (Chen et al, 1991). The virulence determinants on the Rsv1-genotype soybeans have been mapped to HC-Pro and P3, and the gain of virulence by an avirulent SMV requires at least three simultaneous amino acid substitutions: either two in HC-Pro and one in P3, or two in P3 and one in HC-Pro Hajimorad et al, 2008Hajimorad et al, , 2011.…”
Section: Selection Analyses Identified Some Positively Selected Regiomentioning
confidence: 99%
“…It was initially named Rsv and found in PI96983 soybean (Kiihl and Hartwig, 1979) and later renamed Rsv1 (Chen et al, 1991). Subsequent studies on soybean cultivars resistant to SMV revealed additional eight different Rsv1 alleles, from cultivars Ogden, York, Marshall, Kwanggyo, 'Raiden', 'Suweon 97', LR1 and PI507389, respectively (Kiihl and Hartwig, 1979;Buss et al, 1997;Buzzell and Tu, 1989;Chen et al, 1991Chen et al, , 1993Chen et al, , 1994Chen et al, , 2001Chen et al, , 2002Ma et al, 1995;Zheng et al, 2005). The responses of soybeans carrying these Rsv1 alleles to different SMV strains are diverse, ranging from extreme resistance and necrosis to mosaic symptoms.…”
Section: Smv-host Interactionsmentioning
confidence: 99%